Preparedness for practice: Experiences of newly qualified professional nurses in a private hospital setting - Charlene Muruvan; Charlene Downing; Irene J. Kearns (Elsevier, 2021)
Background: Preparedness of newly qualified professional nurses has become a concern in clinical practice. The importance of quality care and patient safety issues in healthcare has increased the expectations of the new professional nurse. The reality of working in a clinical setting for newly qualified professional nurses can prove to be overwhelming, resulting in a lack of confidence in their ability to perform effective patient care. Aim: To explore and describe the lived experiences of preparedness amongst newly qualified professional nurses in a private hospital and make recommendations to support a successful transition into the new role as a professional nurse. Design: A qualitative exploratory descriptive and contextual design. Method: A descriptive phenomenological approach was utilised. Participants were selected through purposive sampling. Data collection was done by conducting eight in-depth individual interviews. Data was analysed using Giorgi's data analysis method. Results: Three themes emerged from this study. Newly qualified professional nurses experienced 1) Lack of preparedness for leadership, responsibility, doubted their own competence. 2) A range of skills was needed to engage with various role players. 3) Time was essential to grow into confident professional nurses. Conclusion: Newly qualified professional nurses encounter numerous trials at the onset of their careers. The transition from student to professional nurse is a vital area in need of support. Practical experience is essential in the transition process for newly qualified professional nurses. These experiences have confirmed the need for attention and support for newly qualified professional nurse within the first year of practice.